A Case Series of 25 Dogs with Chondrosarcoma - Sylvestre, Anne M.; Brash, Marina L.; Atilola, M. A. O.; Cockshutt, Joanne R. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
The purpose of this study was to examine clinical, radiographic and histological features as well as post-diagnosis survival times of 25 dogs with chrondrosarcoma (CS). The diagnoses were made on histological evaluation of surgical biopsies or post-mortem specimens. Mixed breed dogs were found to be at higher risk.Chondrosarcoma of the proximal humerus was the most difficult to diagnose, clinically resembling a nerve sheath tumour and offering few gross abnormalities or radiographic changes. Chrondrosarcoma was transarticular in one case.The histological grading used was not well correlated with survival times; location of the CS seemed to be a better indicator of prognosis. Dogs with CS on a limb had the best survival rates, whereas those with CS of the vertebrae had the worst outcome. Surgery was beneficial in the cases of CS located on facial bones and limbs.The purpose of this paper was to examine the clinical and diagnostic features and survival rates of dogs with chondrosarcoma (CS). Histological diagnoses were made in all cases, mixed breeds were over represented. The location of the tumour was a better prognostic indicator than the histological grading. Dogs with CS on a limb had the longest survival times.
Keywords: Chondrosarcoma; radiation